Kontribusi Mahasiswa Program Kampus Mengajar Angkatan 6 Dalam Meningkatkan Literasi Siswa SDN 11 Bermani Ilir - Pranesti, Andini; Herlina, Meti; Meirani, Meirani; Lisdayanti, Septina (University of Muhammadiyah Sumatera Utara, 2024)
This service is part of the learning and teaching activities in basic education units of the Merdeka Belajar Kampus Merdeka (MBKM) program as an effort to provide opportunities for students to learn outside the classroom by becoming partners with teachers in the learning process in primary and secondary education units, hereinafter referred to as assignment school. The Teaching Campus aims to equip students with a variety of expertise and skills by becoming partners with teachers to innovate in learning, develop strategies and learning models that are creative, innovative and fun. At SDN 11 Bermani Ilir I was placed to be able to serve in introducing literacy and numeracy to students who still have very low levels of literacy and numeracy, especially in the field of technology adaptation, many students are already at a high grade level but cannot yet read and memorize the alphabet. So during our service we try to develop work programs that can help students improve their literacy and numeracy skills, as well as introduce technology that they can use in the learning process, for example creative learning videos.